2017
DOI: 10.4103/0259-1162.206870
|View full text |Cite
|
Sign up to set email alerts
|

A survey of current practice of supraglottic airway devices in pediatric anesthesia from India

Abstract: Background and Objectives:Supraglottic airway devices (SADs) have revolutionized the pediatric anesthetic practice and got a key role in difficult airway (DA) management. Several modifications of SADs design had come up to improve their safety.Aim:The aim of this survey was to determine the current usage of SADs in pediatric anesthetic practice, their availability, and to know any difficulties noted in practice.Methods:It was a questionnaire survey among the anesthesiologists who attended the National Pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In the present study, 30.3% of respondents had available fiberoptic bronchoscope, and 27.9% had experience with children in this technique. SAD are frequently used in pediatric anesthesia [7]. In our study, general anesthesia with LMA in pediatric cases was preferred by 86.7% of participants in the short-term surgeries.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…In the present study, 30.3% of respondents had available fiberoptic bronchoscope, and 27.9% had experience with children in this technique. SAD are frequently used in pediatric anesthesia [7]. In our study, general anesthesia with LMA in pediatric cases was preferred by 86.7% of participants in the short-term surgeries.…”
Section: Discussionmentioning
confidence: 64%
“…First-generation SAD were frequently present (97%), and 64% of the participants preferred to use it for short-term pediatric surgeries. They found that intraoperative displacement (55%) was a common problem and 11% of the participants found aspiration as a problem [7]. In our survey, the frequency of using SAD in pediatric short cases was 86.7% and the causes limiting their use were headed by the inability to do aspiration.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…[ 5 9 ] However, there is a dearth of comprehensive large-scale pan-Indian data. [ 10 ] AAGBI survey focussed mainly on the choice of SGADs and their use in difficult airway. SPA survey concentrated mainly on practice patterns pertaining to LMA family.…”
Section: Discussionmentioning
confidence: 99%